Effects of acupuncture on the brain in primary insomnia: a coordinate-based meta-analysis of fMRI studies - Zang, Shuhan; Chen, Ying; Chen, Haonan; Shi, Huawei; Zhou, Li (Frontiers in Neurology, 2023)
Importance: Primary insomnia (PI) has a high global incidence, and effective treatments with fewer side effects are needed. Acupuncture, a treatment used in traditional Chinese Medicine, has increasingly been as a treatment for PI and is recognized by many doctors and patients. Some evidence has suggested that acupuncture was associated with improvements in objective sleep parameters and might cause changes in some brain regions. Individual studies with limited sample sizes and low detection thresholds may produce false positive results, and no systematic review of the effects of acupuncture in PI has been performed. Objective: The goal of this systematic review and coordinate-based meta-analysis was to summarize the literature on fMRI evaluation of patients with PI treated with acupuncture. Design: We performed methodical and comprehensive searches of multiple publication databases (from initiation until December 2022): Web of Science, PubMed, Science Direct, Embase, Wan Fang, China National Knowledge Infrastructure, and Chinese Scientific Journal Database. Study bias and quality were evaluated by two researchers. Furthermore, seed-based D-mapping with permutation of subject images (SDM-PSI) meta-analysis was applied to explore the central mechanisms behind acupuncture treatment for PI. Results: The analysis included 305 patients with PI from 11 studies. SDM-PSI analysis revealed that patients with PI exhibited elevated amplitudes of regional homogeneity and low-frequency fluctuations in the left superior frontal gyrus, right angular gyrus, and cerebellum. Acupuncture improved the function of right superior frontal gyrus, left inferior frontal gyrus, left inferior temporal gyrus, left supramarginal gyrus, left precuneus, right precuneus, left supplementary motor area, and right parahippocampal gyrus. The brain regions affected by non-acupoint acupuncture were all in the frontal lobe. Conclusion: This coordinate-based meta-analysis revealed that acupuncture in patients with PI had significant effects on the default mode network, particularly the frontal lobe and precuneus, and that non-acupoint acupuncture could offer some benefits to the functioning of frontal brain regions.